Customer Satisfaction Linking Relationship Marketing, Service Quality, and Repurchase Intention at Fore Coffee Bandung - Juwita Khoirunnisa Dzaqia; Arlin Ferlina Mochamad Trenggana (Studi Ilmu Manajemen dan Organisasi, 2026)
Purpose: Through the mediating function of customer satisfaction, this study examines the direct and indirect impacts of relationship marketing and service quality on repurchase intention among Fore Coffee consumers in Bandung, Indonesia. Research Methodology: A quantitative study with purposive sampling was conducted with 150 respondents. An online survey was used to gather data, and Partial Least Squares Structural Equation Modeling (PLS-SEM) with Structural Equation Modeling berbasis Partial Least Squares (SmartPLS) 3.0 was used for analysis. Results: Relationship marketing and service quality strongly influenced customer satisfaction and repurchase intention. Service quality was expected to be the most significant factor among all predictors. Additionally, customer satisfaction serves as an important mediator, particularly in enhancing the impact of service quality on consumers' propensity to make additional purchases. Conclusions: Customer satisfaction is a crucial link that transforms service quality into repeat purchase behavior. Relationship marketing and service quality are important factors that influence customer satisfaction and repurchase intentions. Limitations: This study had a small sample size and was restricted to a particular geographic location. Future studies should broaden their focus and incorporate other factors, such as perceived value and brand image. Contributions: By combining relationship marketing and service quality in the context of Indonesian digital coffee shops, this study provides innovation and empirical data on the mediating function of customer happiness in influencing repurchase intention.